Right-to-Work Laws Revisited: Implications for Human Resource Professionals - Savino , David M. (American Journal of Management, 2021)
After several decades of relatively little movement in the area of Right-to-Work (RTW) laws, the last few years have been very active, as it has reached the top of many political agendas of Midwestern states located in what is known as the rust belt region. With the increased activity of the passage of RTW laws in three Midwestern states over the last four years increased attention is now being paid to the current phenomenon as well as prospects in other industrial states where unions are still very much present. This then brings the key issue to mind as to why this is now occurring and what implications it has on the state of the worker-management relationship for the future.